2020
DOI: 10.1002/anie.202011408
|View full text |Cite
|
Sign up to set email alerts
|

How Oxygen Binding Enhances Long‐Range Electron Transfer: Lessons From Reduction of Lytic Polysaccharide Monooxygenases by Cellobiose Dehydrogenase

Abstract: Long‐range electron transfer (ET) in metalloenzymes is a general and fundamental process governing O2 activation and reduction. Lytic polysaccharide monooxygenases (LPMOs) are key enzymes for the oxidative cleavage of insoluble polysaccharides, but their reduction mechanism by cellobiose dehydrogenase (CDH), one of the most commonly used enzymatic electron donors, via long‐range ET is still an enigma. Using multiscale simulations, we reveal that interprotein ET between CDH and LPMO is mediated by the heme prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 73 publications
2
26
0
Order By: Relevance
“…Organized solvent water molecules were found to be important in mediating electron tunneling across protein–protein interfaces as demonstrated theoretically and experimentally. Indeed, we found that interface regions between the heme domain and ferredoxin domain are highly hydrophilic and populated by plenty of solvent water molecules (Figure a). It is expected that the solvent water molecules can not only mediate the H-bond interactions between the heme domain and ferredoxin domain but also form new ET pathways as exemplified in Figure b.…”
Section: Resultssupporting
confidence: 52%
“…Organized solvent water molecules were found to be important in mediating electron tunneling across protein–protein interfaces as demonstrated theoretically and experimentally. Indeed, we found that interface regions between the heme domain and ferredoxin domain are highly hydrophilic and populated by plenty of solvent water molecules (Figure a). It is expected that the solvent water molecules can not only mediate the H-bond interactions between the heme domain and ferredoxin domain but also form new ET pathways as exemplified in Figure b.…”
Section: Resultssupporting
confidence: 52%
“…Therefore, the spin-regulated ET in the quartet state is remarkably favored over that in the doublet state. 38 Outlook. This Perspective discusses and highlights the critical roles of exchange and superexchange interactions in reactivities of metalloenzymes.…”
supporting
confidence: 88%
“…39−43 The heme of CDH can reduce Cu(II) to Cu(I), whereby the reduced Cu(I) can bind and activate O 2 . In the presence of O 2 , our QM/MM-MD metadynamics reveal that the binding of oxygen to Cu(II) triggers a long-range electron transfer from Fe(II) to Cu(II), 38 which is spin-regulated. Though both the doublet and quartet states are degenerate in energies in the reactant complex, we find that the electron transfer in the quartet state is remarkably favored over the one in the double state, which may not be rationalized by the thermodynamic advantage of ∼5 kcal/mol in the quartet state.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As Fe2 has five parallel electrons, IC4′ will obtain maximum exchange interactions (see Figure c) . Thus, such an inner sphere electron transfer is spin-regulated and exchange-enhanced. ,, …”
Section: Resultsmentioning
confidence: 99%